Penataan Sign Pada Koridor Tunjungan Kota Surabaya Dalam Upaya Perbaikan Kualitas Lingkungan Pusat Kota Dengan Mempertahankan Image Sebagai Kawasan Konservasi Cagar Budaya - Widodo, Ismail Wahyu; Soemardiono, Bambang; Sunarti, Endang Titi (Jurnal Tata Kota dan Daerah, 2014)
Tunjungan area is the center of Surabaya covering Embong Malang - Blauran - Praban - Tunjungan. As a business center, building facade in the area can not be separated from the existence of outdoor advertisement, or in this study, will be named as sign. In fact, private signs outside the buildings alongside the corridor are experiencing visual disharmony order with their facade based on the fact that the buildings are preserved by Heritage Act. As a result, building image along the corridor as heritage preservation area is deteoriating. Therefore, factors, criteria, principles, and arrangement concept of sign arrangement which appropriately match with the image of conservation area are needed. The study consists of image assessment, conservation building character assessment, sign and precedent assessment. The result of the study has four aspects: aesthetic, building, effectiveness, and safety aspects which have their own constituent component. The study is a descriptive research with rationalistic method of approach which combines empirical evidence and building facade arrangement ethics at preservation area. By using Urban Design Methods by Moughtin (1999), four process is carried out in this study: analysis - synthesis - appraisal - decision. The corridor and buildings at the area are analyzed using main technique: Walkthrough Analysis and Character Appraisal. Then the analysis is evaluated and cross checked with the selected references to get criteria, preparation of design concepts, and to provide guidance for the arrangement of building sign along Tunjungan corridor.Through these methods, it can be identified functional design criteria, design concept, and technical referral based on evaluation of arrangement aspects. Based on the assessment, the result of the study are: conservation area representative sign, maintain the integrity of conservation building, effectiveness and efficiency for sign readers, as well as maintaining the safety of road users and the strength of building structure due to the placement of a sign mounted on the building.Keywords: Heritage, Image of Conservation Area, Methods, Sign